TWO NEW SPECIES OF ARGULUS MULLER (CRUSTACEA: BRANCHIURA) FROM RIVER CAUVERY WITH A KEY TO INDIAN SPECIES - Thomas, M M; Devaraj, M (Indian Journal of Fisheries, 2011)
Two new species of Argulus Muller viz., A. fluviatilis and A. cauveriensiscollected from River Cquvery at Hoginekal, South India, are described, with adiscussion on their affinity to the other Indian species. The paper also provides akey to the Indian species of Argulus